O problema do colecionador de cupons: quanto custa completar o álbum de figurinhas da Copa do Mundo? - Rosa, Guilherme Miguel (2019)
This work presents a study on the Coupon Collector’s Problem applied to the challenge of collecting the soccer stickers of the official World Cup album of 2018. The average cost to complete an album is determined by considering different scenarios such as collector collaboration. The obtained solutions are validated through numerical results that simulate the collection process of the stickers.